(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Goiter simply refers to the enlargement of the thyroid gland. It can be due to various causes with the dietary iodine deficiency being the most common cause worldwide. Diffuse toxic goiter consists of a diffusely enlarged, vascular gland with rubber-like consistency. Microscopically, the follicular cells are hypertrophic and hyperplastic with little colloid in them. Lymphocytes and plasma cells infiltrate into the gland and can ultimately aggregate into lymphoid follicles.